2019
DOI: 10.1055/s-0039-1688779
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Extensor Mechanism Disruptions: More Than Double the Trouble?

Abstract: Simultaneous bilateral extensor mechanism disruption (BEMD) is a rare condition, for which the relationship between comorbid conditions, complications, and clinical outcomes has not been well defined. We hypothesized that patients with BEMD would have more comorbidities, more repair failures, and worse clinical outcomes compared with patients with unilateral extensor mechanism disruption (UEMD). We performed a retrospective review of all adult patients seen at our institution for either a quadriceps or patella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Therefore, ruptures of these tendons are uncommon injuries that occur mainly in middle-aged and older aged men. Simultaneous rupture of bilateral quadriceps tendons is rare, accounting for less than 5% of all cases and it's much more difficult to repair than a unilateral tendon rupture [10]. In addition, some research indicated there was an association between patella spurs and quadriceps tendon ruptures, we should pay more attention when the knee radiographs found a patella spur [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ruptures of these tendons are uncommon injuries that occur mainly in middle-aged and older aged men. Simultaneous rupture of bilateral quadriceps tendons is rare, accounting for less than 5% of all cases and it's much more difficult to repair than a unilateral tendon rupture [10]. In addition, some research indicated there was an association between patella spurs and quadriceps tendon ruptures, we should pay more attention when the knee radiographs found a patella spur [11].…”
Section: Discussionmentioning
confidence: 99%
“…So, Transection of these tendons is a rare injury and commonly affecting middle age and elderly men. Moreover, bilateral Simultaneous rupture of quadriceps tendons is rare, contributing to less than 5% of all ruptures of the quadriceps tendon and it’s more difficult to manage than a unilateral tendon rupture ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…A rutura bilateral crónica do tendão quadricipital é descrita como sendo de difícil tratamento e de longo período de recuperação. 12 O seu tratamento deve ser seguido de reabilitação funcional intensiva. 2 O diagnóstico e tratamento precoces são habitualmente descritos em associação a melhor resultado funcional.…”
Section: Discussionunclassified